GULMA TITHONIA DIVERSIFOLIA INSITU PENDUKUNG PERTANIAN ORGANIK SECARA BERKELANJUTAN - Yadi Jufri; Syafrimen Yasin; Agustian Agustian; Teguh Budi Prasetyo; Nurhajati Hakim (Prosiding Seminar Nasional USM, 2019)
Tithonia diversifolia is a weed that can be used as a source of organic material in situ to support organic agriculture in a sustainable manner. The purpose of this paper is to introduce techniques to prepare sources of in situ organic material with Tithonia diversifolia weed plants in a sustainable manner. Tithonia diversifolia weeds contain high N and K nutrients up to 4.5% and can be pruned every 2 months with a large amount of biomass that can be used as a source of organic material in the form of green fertilizer or compost with good quality and enough available throughout the growing season. The preparation technique is done in two ways, namely by cultivating aisle and cultivating a garden circle. The results showed that the provision of Tithonia diversifolia in the form of compost was able to reduce the amount of Urea and KCl fertilizer as much as 50% of its needs with corn production of 6.68 tons / ha and soybean production of 1.80 tons / ha. Tithonia diversifolia is easy to grow anywhere with poor land conditions even with a fairly good level of adaptation.